Oxford Reading Tree Viking Adventure for Grade 1 - Roderick Hunt; Roderick Hunt (Karachi Oxford University Press, 2025)
Read the title and look through the pictures to find out about the Vikings. You may need to explain that the Vikings were people who travelled across the North $1! =s